COMPARATIVE DEMOGRAPHICS OF THE WITWATERSRAND BRANCH OF THE SOUTH AFRICAN INSTITUTE OF INDUSTRIAL ENGINEERS - Snaddon, D.R. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This paper researches demographic characteristics of members of the Witwatersrand branch of the South African Institute of Industrial Engineers. It draws comparisons between members and other groups of graduates concerning age, highest educational qualification, geographical place of employment, sector and type of industry. Then the type of tasks that IEs undertake is discussed both within and outside "engineering". AFRIKAANSE OPSOMMING: Die demografiese eienskappe van lede van die Witwatersrandse tak van die suid-Afrikaanse Instituut van Bedryfsingenieurs word in die artikel ontleed. Verskille in ouderdom, hoogste akademiese prestasie, geografiese gebied waar in diens, asook sektor en tipe nywerheid, tussen lede en ander gegradueerders word bespreek. Daarna is die aktiwi teite, wat bedryfsingenieurs onderneem, beide binne en buite "ingenieurswerk" bespreek.